2020
DOI: 10.1101/2020.04.04.025411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycobacterium tuberculosisstimulates IL-1β production by macrophages in an ESAT-6 dependent manner with the involvement of serum amyloid A3

Abstract: TX 75708-3154, phone 29 (903)-877-7665, fax (903) 877-5516, buka.samten@uthct.edu 30 4. Acknowledgment: We thank Dr. Charles A. Dinarello for his thoughtful guidance and 31 discussions.32 5. Brief summary: Mycobacterium tuberculosis stimulated the production of IL-1β by 33 macrophages and in mouse lungs with the activation of NLRP3 and K+ efflux in an ESAT-6 34 dependent manner with the involvement of SAA3. 35 36 37 38 39 40 41 42 43 44 45 46 3 ABSTRACT 47To explore interleukin (IL)-1β production in tuberculos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Lee et al have revealed that the activation of primary murine microglia in conditioned media from M.tb-infected macrophages was associated with the maturation of caspase-1 and IL-1b in microglia during the M.tb infection (109). Generally, M.tb could be maintained in a silencing status by regulating the expression of interleukins in the homeostatic immune response (154,155). Moreover, signal transducer and activator of transcription 1 (Stat1) and interferon regulatory factor1 (IRF1) have been verified to be involved in the inflammation response of macrophages and microglia after TBM induced by attenuated M.tb (74).…”
Section: Interaction Of the Microglia With Cns Macrophages In Tbmmentioning
confidence: 99%
“…Lee et al have revealed that the activation of primary murine microglia in conditioned media from M.tb-infected macrophages was associated with the maturation of caspase-1 and IL-1b in microglia during the M.tb infection (109). Generally, M.tb could be maintained in a silencing status by regulating the expression of interleukins in the homeostatic immune response (154,155). Moreover, signal transducer and activator of transcription 1 (Stat1) and interferon regulatory factor1 (IRF1) have been verified to be involved in the inflammation response of macrophages and microglia after TBM induced by attenuated M.tb (74).…”
Section: Interaction Of the Microglia With Cns Macrophages In Tbmmentioning
confidence: 99%
“…Pharmacological inhibition of TLR2 and TWIK2 C29 (MedChemExpress) and quinine (Sigma) were used as TLR2-selective inhibitors (20) and TWIK2selective inhibitors (21,22), respectively. PBMCs from healthy volunteers were stimulated with 10 µg/ml heat-killed MAC antigens in the presence or absence of various concentrations (10, 50 and 100 µM) of C29 or quinine at 37 °C in 5% CO 2 for 24 h. CD14+ monocytes from healthy volunteers were stimulated with live MAC (MOI of 10) in the presence or absence of various concentrations (10, 50 and 100 µM) of C29 or quinine at 37 °C in 5% CO 2 for 18 h. The cell-free supernatants were collected and stored at -80 °C until use.…”
Section: Multiplex Immunoassaymentioning
confidence: 99%
“…TLR2, P2X7R and two-pore domain potassium (K+) e ux channels are involved in mycobacteria-induced proin ammatory signaling, especially IL-1β production (22,26,27). To determine whether any of these receptors and channels are involved in reduced IL-1β, IL-18, IL-1α and IL-10 production, we cultured PBMCs of NTMPD patients and their healthy household contacts with or without heat-killed M. intracellulare as mentioned in the methods section.…”
Section: Ntmpd Patients Have a Defective Expression Of Tlr2 And Twik2mentioning
confidence: 99%